A qualitative examination of bi/multilingual counselor training and experiences. (23rd November 2021) - Pope, Amber L.; Sunal, Zahide; Gantt, Alexandra C.; Zimmerman, Betsy; Corey, Ali K.; Nuosce, Mary; Araujo, Lourdes
Abstract: There is an increased need for bi/multilingual counseling services to meet the growing linguistic diversity of the US population. Despite this need, the counseling profession has made little progress on systemically integrating language factors and bi/multilingual counseling skills into counselor training and professional development. Using consensual qualitative research (CQR), we interviewed 14 bi/multilingual counselors (BMCs) and identified five domains: counseling experience, counselor training and preparation (during master's), supervision and continuing education (post master's), recommendations, and other bi/multilingual counseling‐related experience. These domains provide insight into BMCs' clinical experiences and training, along with strategies to improve counselor education, professional development, and resources for BMCs. Implications for counseling and counselor education, limitations, and suggestions for future research are discussed.